Appropriate use of cancer comprehensive genome profiling assay using circulating tumor DNA. Issue 9 (12th July 2021) - Sunami, Kuniko; Bando, Hideaki; Yatabe, Yasushi; Naito, Yoichi; Takahashi, Hideaki; Tsuchihara, Katsuya; Toyooka, Shinichi; Mimori, Koshi; Kohsaka, Shinji; Uetake, Hiroyuki; Kinoshita, Ichiro; Komine, Keigo; et al.
Abstract: Comprehensive genomic profiling (CGP) is being increasingly used for the routine clinical management of solid cancers. In July 2018, the use of tumor tissue‐based CGP assays became available for all solid cancers under the universal health insurance system in Japan. Several restrictions presently exist, such as patient eligibility and limitations on the opportunities to perform such assays. The clinical implementation of CGP based on plasma circulating tumor DNA (ctDNA) is also expected to raise issues regarding the selection and use of tissue DNA and ctDNA CGP. A Joint Task Force for the Promotion of Cancer Genome Medicine comprised of three Japanese cancer‐related societies has formulated a policy proposal for the appropriate use of plasma CGP (in Japanese), available at https://www.jca.gr.jp/researcher/topics/2021/files/20210120.pdf, http://www.jsco.or.jp/jpn/user_data/upload/File/20210120.pdf, and https://www.jsmo.or.jp/file/dl/newsj/2765.pdf . Based on these recommendations, the working group has summarized the respective advantages and cautions regarding the use of tissue DNA CGP and ctDNA CGP with reference to the advice of a multidisciplinary expert panel, the preferred use of plasma specimens over tissue, and multiple ctDNA testing. These recommendations have been prepared to maximize the benefits of performing CGP assays and might be applicable in other countries and regions.